ScarNet: Development and Validation of a Novel Deep CNN Model for Acne Scar Classification With a New Dataset - Junayed, Masum Shah; Islam, Md Baharul; Jeny, Afsana Ahsan; Sadeghzadeh, Arezoo; Biswas, Topu; Shah, A. F. M. Shahen (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Acne scarring occurs in 95% of people with acne vulgaris due to collagen loss or gains when the body is healing the damages of the skin caused by acne inflammation. Accurate classification of acne scars is a vital factor in providing a timely, effective treatment protocol. Dermatologists mainly recognize the type of acne scars manually based on visual inspections, which are time- and energy-consuming and subject to intra- and inter-reader variability. In this paper, a novel automated acne scar classification system is proposed based on a deep Convolutional Neural Network (CNN) model. First, a dataset of 250 images from five different classes is collected and labeled by four well-experienced dermatologists. The pre-processed input images are fed into our proposed model, namely ScarNet, for deep feature map extraction. The optimizer, loss function, activation functions, filter and kernel sizes, regularization methods, and the batch size of the proposed architecture are tuned so that the classification performance is maximized while minimizing the computational cost. Experimental results demonstrate the feasibility of the proposed method with accuracy, specificity, and kappa score of 92.53%, 95.38%, and 76.7%, respectively.
Keywords: Skin; Feature extraction; Convolutional neural networks; Support vector machines; Diseases; Computational modeling; Kernel; Acne scars; dataset; image classification; CNN; skin disorder; skin image analysis; EPIDEMIOLOGY; Computer Science; Engineering; Telecommunications